1996
DOI: 10.1002/(sici)1096-9071(199602)48:2<121::aid-jmv1>3.3.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of the laboratory rat with the hepatitis E virus

Abstract: To confirm an earlier report that laboratory rats are susceptible to infection with the hepatitis E virus (HEV), we inoculated 27 Wistar rats intravenously with a suspension of a human stool known to contain infectious HEV. Stool, sera, and various tissues were collected from three rats each on days 0 (preinoculation) and 4, 7, 11, 14, 18, 21, 25, 28, and 35 postinoculation. Stool and sera specimens were examined by reverse transcription-polymerase chain reaction for the presence of HEV genomic sequences. Tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
2
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 0 publications
1
36
2
3
Order By: Relevance
“…Trials to experimentally infect laboratory rats or mice with human HEV led to contradictory results, because some studies reported successful infection and others did not. 27,28 Recently, an HEV-related agent was detected from wild rats, and sequence comparison to human and avian HEV strains revealed only 59.9% and 49.9% nucleotide identity, respectively. 29 The low nucleotide sequence identities between rat HEV and human HEV may indicate an independent evolution of both viruses with no transmission between both hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Trials to experimentally infect laboratory rats or mice with human HEV led to contradictory results, because some studies reported successful infection and others did not. 27,28 Recently, an HEV-related agent was detected from wild rats, and sequence comparison to human and avian HEV strains revealed only 59.9% and 49.9% nucleotide identity, respectively. 29 The low nucleotide sequence identities between rat HEV and human HEV may indicate an independent evolution of both viruses with no transmission between both hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Trials to infect laboratory rats or mice experimentally with human HEV led to contradictory results, as some studies reported successful infection whilst others did not (Karetnyï et al, 1993;Li et al, 2008;Maneerat et al, 1996). Several studies have shown the detection of HEV-specific antibodies in rodents from different countries including India, Vietnam, Brazil, Japan and the USA, including commensal rodents such as Norway (Rattus norvegicus) and black (Rattus rattus) rats, but also wild rodents such as deer mouse (Peromyscus maniculatus) and cotton rat (Sigmodon hispidus) (Arankalle et al, 2001;Favorov et al, 2000;Hirano et al, 2003;Kabrane-Lazizi et al, 1999;Meng et al, 2002;Vitral et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…HEV-specific antibodies as well as viral RNA have been detected in several animal species (Smith, 2001;Meng, 2009 An initial indication for a potential role of rodents in the transmission of hepatitis E was found by the detection of HEV antigen in the sera of rodents caught next to a Russian village where an outbreak of hepatitis E was reported (Karetnyï et al, 1993). Trials to infect laboratory rats or mice experimentally with human HEV led to contradictory results, as some studies reported successful infection whilst others did not (Karetnyï et al, 1993;Li et al, 2008;Maneerat et al, 1996). Several studies have shown the detection of HEV-specific antibodies in rodents from different countries including India, Vietnam, Brazil, Japan and the USA, including commensal rodents such as Norway (Rattus norvegicus) and black (Rattus rattus) rats, but also wild rodents such as deer mouse (Peromyscus maniculatus) and cotton rat (Sigmodon hispidus) (Arankalle Favorov et al, 2000;Hirano et al, 2003;Kabrane-Lazizi et al, 1999; Meng et al, 2002;Vitral et al, 2005).…”
mentioning
confidence: 99%
“…It has been suspected that HEV might replicate in tissues and organs other than the liver (2). Recent results from studies performed with rats infected with human HEV have suggested that the virus may replicate extrahepatically (20). The objectives of this study are to utilize swine as a model system to systematically study HEV replication and to identify potential extrahepatic sites of HEV replication.…”
mentioning
confidence: 99%